Prevalence Of Piriformis Muscle Syndrome Among Individuals with Low Back Pain: Piriformis Muscle Syndrome Among Individuals with Low Back Pain - Islam, Farooq; Mansha, Hamza; Gulzar, Khushboo; Raza, Asim; Raffique, Awais; Haider, Saqlain (Pakistan Journal of Health Sciences, 2022)
Piriformis syndrome is a condition in which the piriformis muscle, located in the buttock region, spasms and causes buttock pain. The piriformis muscle also can irritate the nearby sciatic nerve and cause pain, numbness and tingling. Starts at the lower spine and connects the upper surface of each femur (thighbone). Functions to assist in rotating the hip and turning the leg and foot outward Runs diagonally. Objective: To find out the prevalence of piriformis muscle syndrome among individuals with low back pain. Methods: Participation of population from Gujranwala city from various emergency clinics was remembered for this study in view of inclusion and exclusion criteria. The data was collected through non-probability convenient sampling technique. Affirmed instances of low back torment patients were added and get some information about their agony as indicated by VAS (visual simple scale) and outer muscle tests (FAIR test, pace sign, Piriformis stretch (test) were performed on patients. Results: The results have been obtained from 219 participants. The overall Prevalence of piriformis muscle syndrome among individuals with low back pain was 18.3%.The Mean±SD of exact BMI were 27.43±6.859. Out of 219 patients, male and female Pace sign were respectively (85.8% negative and 14.2% positive). (81.7%) Negative and (18.3%) Positive Prevalence of piriformis muscle syndrome in the general population in Age groups chi-square value is (47.753b) and P- Value (<0.001*). Conclusions: In this research, the positive prevalence rate is 18.3%. It demonstrates that several individuals with low back pain have piriformis muscle syndrome.